Design, synthesis and photochemical properties of the first examples of iminosugar clusters based on fluorescent cores - Lepage, Mathieu L.; Mirloup, Antoine; Ripoll, Manon; Stauffert, Fabien; Bodlenner, Anne; Ziessel, Raymond; Compain, Philippe (Beilstein Journal of Organic Chemistry, 2015)
The synthesis and photophysical properties of the first examples of iminosugar clusters based on a BODIPY or a pyrene core are reported. The tri- and tetravalent systems designed as molecular probes and synthesized by way of Cu(I)-catalysed azide–alkyne cycloadditions are fluorescent analogues of potent pharmacological chaperones/correctors recently reported in the field of Gaucher disease and cystic fibrosis, two rare genetic diseases caused by protein misfolding.
Keywords: BODIPY; fluorescent probes; iminosugars; 4-methylumbelliferone; multivalency; pyrene

Iminosugars: from Synthesis to Therapeutic Applications - Compain, P.; Martin, O. R. (Wiley & Sons, 2007)

Iminosugars as Glycosidase Inhibitors: Nojirimycin and Beyond - Stütz, A. E. (Wiley-VCH, 1999)

(untitled) - Moriyama, H.; Tsukida, T.; Inoue, Y.; Yokota, K.; Yoshino, K.; Kondo, H.; Miura, N.; Nishimura, S.-I. (J. Med. Chem., 2004)

(untitled) - Orsato, A.; Barbagallo, E.; Costa, B.; Olivieri, S.; De Gioia, L.; Nicotra, F.; La Ferla, B. (Eur. J. Org. Chem., 2011)

(untitled) - Decroocq, C.; Stauffert, F.; Pamlard, O.; Oulaïdi, F.; Gallienne, E.; Martin, O. R.; Guillou, C.; Compain, P. (Bioorg. Med. Chem. Lett., 2015)

(untitled) - Winchester, B. G. (Tetrahedron: Asymmetry, 2009)

(untitled) - Horne, G.; Wilson, F. X. (Prog. Med. Chem., 2011)

(untitled) - Nash, R. J.; Kato, A.; Yu, C.-Y.; Fleet, G. W. J. (Future Med. Chem., 2011)

(untitled) - Compain, P.; Bodlenner, A. (ChemBioChem, 2014)

(untitled) - Gouin, S. G. (Chem. – Eur. J., 2014)

(untitled) - Compain, P.; Decroocq, C.; Iehl, J.; Holler, M.; Hazelard, D.; Mena Barragán, T.; Ortiz Mellet, C.; Nierengarten, J.-F. (Angew. Chem., Int. Ed., 2010)

(untitled) - Decroocq, C.; Rodríguez-Lucena, D.; Russo, V.; Mena Barragán, T.; Ortiz Mellet, C.; Compain, P. (Chem. – Eur. J., 2011)

(untitled) - Decroocq, C.; Joosten, A.; Sergent, R.; Mena Barragán, T.; Ortiz Mellet, C.; Compain, P. (ChemBioChem, 2013)

(untitled) - Joosten, A.; Schneider, J. P.; Lepage, M. L.; Tarnus, C.; Bodlenner, A.; Compain, P. (Eur. J. Org. Chem., 2014)

(untitled) - Bonduelle, C.; Huang, J.; Mena-Barragán, T.; Ortiz Mellet, C.; Decroocq, C.; Etamé, E.; Heise, A.; Compain, P.; Lecommandoux, S. (Chem. Commun., 2014)

(untitled) - Lepage, M. L.; Meli, A.; Bodlenner, A.; Tarnus, C.; De Riccardis, F.; Izzo, I.; Compain, P. (Beilstein J. Org. Chem., 2014)

(untitled) - Marradi, M.; Cicchi, S.; Sansone, F.; Casnati, A.; Goti, A. (Beilstein J. Org. Chem., 2012)

(untitled) - Cardona, F.; Isoldi, G.; Sansone, F.; Casnati, A.; Goti, A. (J. Org. Chem., 2012)

(untitled) - Brissonet, Y.; Ortiz Mellet, C.; Morandat, S.; Garcia Moreno, M. I.; Deniaud, D.; Matthews, S. E.; Vidal, S.; Šesták, S.; El Kirat, K.; Gouin, S. G. (J. Am. Chem. Soc., 2013)

(untitled) - Rísquez-Cuadro, R.; García Fernández, J. M.; Nierengarten, J.-F.; Ortiz Mellet, C. (Chem. – Eur. J., 2013)

(untitled) - Moreno-Clavijo, E.; Carmona, A. T.; Moreno-Vargas, A. J.; Molina, L.; Wright, D. W.; Davies, G. J.; Robina, I. (Eur. J. Org. Chem., 2013)

(untitled) - D’Adamio, G.; Parmeggiani, C.; Goti, A.; Moreno-Vargas, A. J.; Moreno-Clavijo, E.; Robina, I.; Cardona, F. (Org. Biomol. Chem., 2014)

(untitled) - Marra, A.; Zelli, R.; D’Orazio, G.; La Ferla, B.; Dondoni, A. (Tetrahedron, 2014)

(untitled) - Decroocq, C.; Rodríguez-Lucena, D.; Ikeda, K.; Asano, N.; Compain, P. (ChemBioChem, 2012)

(untitled) - Joosten, A.; Decroocq, C.; de Sousa, J.; Schneider, J. P.; Etamé, E.; Bodlenner, A.; Butters, T. D.; Compain, P. (ChemBioChem, 2014)

(untitled) - Compain, P.; Decroocq, C.; Joosten, A.; de Sousa, J.; Rodríguez-Lucena, D.; Butters, T. D.; Bertrand, J.; Clément, R.; Boinot, C.; Becq, F.; Norez, C. (ChemBioChem, 2013)

(untitled) - Gavrin, L. K.; Denny, R. A.; Saiah, E. (J. Med. Chem., 2012)

(untitled) - Gomes, C. M. (Curr. Top. Med. Chem., 2012)

(untitled) - Ribeiro-Viana, R.; García-Vallejo, J. J.; Collado, D.; Pérez-Inestrosa, E.; Bloem, K.; van Kooyk, Y.; Rojo, J. (Biomacromolecules, 2012)
See for examples of glycoclusters with a BODIPY tag and see ref. [30].

(untitled) - Hoogendoorn, S.; van Puijvelde, G. H. M.; Kuiper, J.; van derMarel, G. A.; Overkleeft, H. S. (Angew. Chem., Int. Ed., 2014)

(untitled) - Ziessel, R.; Ulrich, G.; Harriman, A. (New J. Chem., 2007)

(untitled) - Loudet, A.; Burgess, K. (Chem. Rev., 2007)

(untitled) - Ulrich, G.; Ziessel, R.; Harriman, A. (Angew. Chem., Int. Ed., 2008)

(untitled) - Boens, N.; Leen, V.; Dehaen, W. (Chem. Soc. Rev., 2012)

(untitled) - Willems, L. I.; Beenakker, T. J. M.; Murray, B.; Scheij, S.; Kallemeijn, W. W.; Boot, R. G.; Verhoek, M.; Donker-Koopman, W. E.; Ferraz, M. J.; van Rijssel, E. R.; Florea, B. I.; Codée, J. D. C.; et al. (J. Am. Chem. Soc., 2014)

(untitled) - Yadav, A. K.; Shen, D. L.; Shan, X.; He, X.; Kermode, A. R.; Vocadlo, D. J. (J. Am. Chem. Soc., 2015)

(untitled) - Davison, H. R.; Taylor, S.; Drake, C.; Phuan, P.-W.; Derichs, N.; Yao, C.; Jones, E. F.; Sutcliffe, J.; Verkman, A. S.; Kurth, M. J. (Bioconjugate Chem., 2011)

U.S. Patent - Haugland, R. P.; Kang, H. C. (1998)

(untitled) - Thoresen, L. H.; Kim, H.; Welch, M. B.; Burghart, A.; Burgess, K. (Synlett, 1998)

(untitled) - Goze, C.; Ulrich, G.; Charbonnière, L.; Ziessel, R. (Chem. – Eur. J., 2003)

(untitled) - Qin, W.; Baruah, M.; Van der Auweraer, M.; De Schryver, F. C.; Boens, N. (J. Phys. Chem. A, 2005)

(untitled) - Ulrich, G.; Goze, C.; Guardigli, M.; Roda, A.; Ziessel, R. (Angew. Chem., Int. Ed., 2005)

(untitled) - Kim, H.; Burghart, A.; Welch, M. B.; Reibenspies, J.; Burgess, K. (Chem. Commun., 1999)

(untitled) - Chen, J.; Reibenspies, J.; Derecskei-Kovacs, A.; Burgess, K. (Chem. Commun., 1999)

(untitled) - Rurack, K.; Kollmannsberger, M.; Daub, J. (New J. Chem., 2001)

(untitled) - Rurack, K.; Kollmannsberger, M.; Daub, J. (Angew. Chem., Int. Ed., 2001)

(untitled) - Ziessel, R.; Harriman, A. (Chem. Commun., 2011)

(untitled) - Ziessel, R.; Ulrich, G.; Haefele, A.; Harriman, A. (J. Am. Chem. Soc., 2013)

(untitled) - Turfan, B.; Akkaya, E. U. (Org. Lett., 2002)

(untitled) - Bricks, J. L.; Kovalchuk, A.; Trieflinger, C.; Nofz, M.; Büschel, M.; Tolmachev, A. I.; Daub, J.; Rurack, K. (J. Am. Chem. Soc., 2005)

(untitled) - Han, J.; Loudet, A.; Barhoumi, R.; Burghardt, R. C.; Burgess, K. (J. Am. Chem. Soc., 2009)

(untitled) - Hansen, J. S.; Ficker, M.; Petersen, J. F.; Christensen, J. B.; Hoeg-Jensen, T. (Tetrahedron Lett., 2013)

(untitled) - Bernhardt, S.; Kastler, M.; Enkelmann, V.; Baumgarten, M.; Müllen, K. (Chem. – Eur. J., 2006)

(untitled) - Somerharju, P. (Chem. Phys. Lipids, 2002)

(untitled) - Pownall, H. J.; Smith, L. C. (Chem. Phys. Lipids, 1989)

(untitled) - Leen, V.; Leemans, T.; Boens, N.; Dehaen, W. (Eur. J. Org. Chem., 2011)

(untitled) - Hornillos, V.; Amat-Guerri, F.; Acuña, A. U. (J. Photochem. Photobiol., A: Chem., 2012)

(untitled) - Mula, S.; Ulrich, G.; Ziessel, R. (Tetrahedron Lett., 2009)

(untitled) - Bura, T.; Ziessel, R. (Org. Lett., 2011)

(untitled) - Bonardi, L.; Ulrich, G.; Ziessel, R. (Org. Lett., 2008)

(untitled) - Jahnke, E.; Weiss, J.; Neuhaus, S.; Hoheisel, T. N.; Frauenrath, H. (Chem. – Eur. J., 2009)

(untitled) - Sonogashira, K.; Tohda, Y.; Hagihara, N. (Tetrahedron Lett., 1975)

(untitled) - Isobe, H.; Fujino, T.; Yamazaki, N.; Guillot-Nieckowski, M.; Nakamura, E. (Org. Lett., 2008)

(untitled) - Valenzano, K. J.; Khanna, R.; Powe, A. C., Jr; Boyd, R.; Lee, G.; Flanagan, J. J.; Benjamin, E. R. (Assay Drug Dev. Technol., 2011)

(untitled) - Chen, T.; Boyer, J. H.; Trudell, M. L. (Heteroat. Chem., 1997)

(untitled) - Sathyamoorthi, G.; Wolford, L. T.; Haag, A. M.; Boyer, J. H. (Heteroat. Chem., 1994)

(untitled) - Burghart, A.; Kim, H.; Wech, M. B.; Thoresen, L. H.; Reibenspies, J.; Burgess, K. (J. Org. Chem., 1999)

(untitled) - Potts, K. T. (Chem. Rev., 1961)

(untitled) - Niu, S.-L.; Ulrich, G.; Retailleau, P.; Harrowfield, J.; Ziessel, R. (Tetrahedron Lett., 2009)

(untitled) - Niu, S. L.; Ulrich, G.; Ziessel, R.; Kiss, A.; Renard, P.-Y.; Romieu, A. (Org. Lett., 2009)

Handbook of Fluorescence Spectra of Aromatic Molecules - Berlman, I. B. (Academic Press, 1971)

(untitled) - Geiger, M. W.; Turro, N. J. (Photochem. Photobiol., 1975)

(untitled) - Kaur, M.; Choi, D. H. (Chem. Soc. Rev., 2015)

(untitled) - Chen, R. F. (Anal. Lett., 1968)

(untitled) - Stern, O.; Volmer, M. (Phys. Z., 1919)